Can universal preschool increase the labor supply of mothers? - Sarah Cattan (IZA World of Labor, 2016)
Since the 1970s, many countries have established free or highly subsidized education for all preschool children in the hope of improving children's learning and socio-economic life chances and encouraging mothers to join the labor force. Evaluations reveal that these policies can increase maternal employment in the short term and may continue to do so even after the child is no longer in preschool by enabling mothers to gain more job skills and increase their attachment to the labor force. However, their effectiveness depends on the policy design, the country context, and the characteristics of mothers of preschoolers.
Keywords: J21; 330; preschool; universal preschool; female labor supply; maternal employment